A Research Environment 2 km Deep-Underground Impacts Embryonic Development in Lake Whitefish (Coregonus clupeaformis) - Pirkkanen, Jake; Zarnke, Andrew M.; Laframboise, Taylor; Lees, Simon J.; Tai, T. C.; Boreham, Douglas R.; Thome, Christopher (Frontiers in Earth Science, 2020)
Biological research conducted in deep-underground environments is limited due to the lack of scientific infrastructure to accommodate the investigations, and only a few studies have utilized complex whole organism models. In this study, lake whitefish (Coregonus clupeaformis) embryogenesis was examined in two different unique laboratory environments; at the Earth’s surface and 2 km deep underground shielded from cosmic radiation. Established developmental endpoints and morphometric analysis were utilized to investigate differences between lake whitefish embryos reared in these two laboratories. No significant differences were observed between the surface and underground laboratories with respect to the timing of hatch or percent survival. However, a significant increase in body length and body weight of up to 10% was observed in embryos reared underground. These findings have been interpreted and discussed in the context of the novel research challenges faced in an inherently difficult to control deep-underground environment. This study represents one of the few investigations with an established whole organism model deep-underground and provides an opportunity to discuss the highly unique technical and logistical challenges of conducting biological experiments in this novel field of scientific research.